INTERNALISASI NILAI-NILAI TAUHID DALAM KESEHATAN MENTAL - Kastolani Kastolani (INJECT (Interdisciplinary Journal of Communication), 2016)
For a Muslim, the most important and foremost to reach a healthy mental is to establish, strengthen, and establish the belief and unity of God that exists within him. Because, with a strong, or solid, and steady belief and unity of God, his soul will always be stable, his mind remains calm, and his emotion is under control. The role of unity of God gives calmness and serenity of soul that at least consists of five things; (a) Feeling like to be loved and cherished which is needed by every person in life and existence. (b) Feeling safety is every person’s needs within him physically and mentally. (c) Self esteem sense means everyone has self esteem in order to be respected by others. (d) Curiosity or recognizing something, where someone has curiosity instinct. (e) Sense of being successful, everyone wants his life to be successful that will bring happiness.Abstrak Bagi seorang muslim, usaha yang paling penting dan utama untuk menuju mental yang sehat adalah memantapkan, menguatkan, dan mengokohkan akidah atau tauhid yang ada dalam dirinya. Sebab, dengan akidah atau tauhid yang kuat, ko koh, dan mantap, jiwanya akan selalu stabil, pikirannya tetap tenang, dan emosi   nya terkendali. Peranan tauhid memberikan ketenangan dan ketenteraman jiwa setidaknya ada lima hal yaitu; (a) Perasaan ingin dikasihi dan disayangi merupakan hal yang sangat dibutuhkan oleh setiap insan dalam hidup dan kehidupannya. (b) Perasaan aman merupakan kebutuhan setiap orang dalam dirinya, baik lahir maupun batin. (c) Rasa harga diri artinya setiap orang memiliki, agar dirinya dihargai orang lain. (d) Rasa ingin tahu atau mengenal sesuatu, seseorang mempunyai naluri ingin tahu. (e) Rasa ingin sukses, setiap orang ingin dalam kehidupannya mengalami keberhasilan yang akan membawa kebahagiaan.